2011
DOI: 10.1519/jsc.0b013e3181bde2cf
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Position on the Percentage of Body Mass Supported During Traditional and Modified Push-up Variants

Abstract: The push-up is a popular upper-extremity weight-bearing exercise. However, limited information is available regarding its effectiveness. Much of the past research has focused on muscle activation levels, whereas very little has examined the forces encountered during push-up variants. The purpose of the present study was to examine the effect of position within the range of motion on the percentage of body mass (BM) supported by the upper extremities during the traditional and modified (knees-down) push-up. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
31
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 25 publications
8
31
1
5
Order By: Relevance
“…The EMG activity and right elbow angle of a participant exemplify this pattern (Figure 2). These data support the findings of Suprak et al, 3 who recorded a greater percentage of body mass supported by the hands in the down position versus the up position.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The EMG activity and right elbow angle of a participant exemplify this pattern (Figure 2). These data support the findings of Suprak et al, 3 who recorded a greater percentage of body mass supported by the hands in the down position versus the up position.…”
Section: Discussionsupporting
confidence: 91%
“…3 The analysis of a large sample of muscle and handposition variants resulted in useful information on the effort required for each of the push-up variants. If the aim of the athlete is to focus on the pectoralis and triceps muscles, the NB is preferred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16,17 Authors 8,11,14 have consistently reported that agonist muscle activation increases with the intensity of the exercise variant. However, the activation levels of the serratus anterior and upper trapezius, the primary scapular stabilizers, across push-up variants appear to depend on hand position and joint angles during the movement (resulting from changing muscle lengths and moment arms) as well as the support surface used.…”
mentioning
confidence: 99%
“…9,12,15,18 Also, activation levels of the scapularstabilizer muscles during the many push-up variants may depend on a complex interplay between the weight-bearing demand of the exercise and the degree of arm elevation. 17 Considering the importance of scapular positioning during strengthening and rehabilitation exercises and the attention paid to corresponding activation levels of the scapular stabilizers in the literature, it is surprising that few investigators have examined scapular kinematics during push-up variants. In the only other study of scapular kinematics during a push-up exercise, Lunden et al 19 reported that, during a push-up with a plus performed against a wall, the scapula began the concentric phase in internal rotation, UR, and anterior tilt and exhibited increasing internal rotation and decreasing UR, with no significant change in PT through the plus phase.…”
mentioning
confidence: 99%